Peran Hukum dalam Pembentukan Kebijakan Politik dalam Konteks Demokrasi Indonesia: Analisis terhadap Legislasi dan Regulasi Pemilu - Nara Amalia; Wahyudi Hidayat; Retno Wulan (SIMPUL: Jurnal Ilmu Politik dan Hukum, 2026)
This study examines the role of law in the formation of political policy in Indonesia, with a focus on election legislation and regulations as key instruments for strengthening democracy. In Indonesia’s democratic system, the law plays a vital role in ensuring that political processes are conducted fairly, transparently, and in accordance with the democratic principles enshrined in the constitution. This article analyzes how legislation, particularly that related to elections, can influence the resulting political policies, as well as its impact on the quality of democracy. This study employs a qualitative method with a case study approach to the electoral legislative process in Indonesia, encompassing the roles of various state institutions, political parties, and civil society. The research findings indicate that although there have been efforts to improve the electoral system through regulatory changes, significant challenges remain in ensuring fair and equitable implementation of the law, particularly in addressing the practice of political corruption and unequal access to political participation. Therefore, strengthening electoral laws and regulations to make them more effective is key to ensuring that the resulting political policies truly reflect the will of the people.